Epidemiology of proximal humerus fractures - Launonen, Antti P.; Lepola, Vesa; Saranko, Aino; Flinkkilä, Tapio; Laitinen, Minna; Mattila, Ville M. (Archives of osteoporosis, 2015)
Summary There are only a few previous population-based studies that include both inpatient and outpatient treatment data. The aim of this study was to investigate the epidemiology of proximal humerus fractures. The incidence of proximal humerus fractures increases with age, and we observe a seasonal variation strongly favoring winter months. Purpose Proximal humerus fractures are the third most common osteoporotic fracture type observed in elderly patients, after wrist and hip fractures. However, few previous population-based studies include both inpatient and outpatient treatment data. The aim of this study was to investigate the incidence, fracture morphology, and treatment method provided in cases of proximal humerus fractures. Methods We retrospectively studied patient records from a mid-sized town in Finland between the years 2006 and 2010. The following data were collected from the medical records: age, sex, date of the fracture, laterality of the fracture, mechanism of injury, treatment method, and other associated fractures at the time of the original injury. Sex and age distributions of the patient population at risk (>18 years old) were calculated for the study period. Results A total of 678 patients (females n = 503, 73 %) with 692 proximal humerus fractures were identified. The unadjusted incidence was 82 (95 % CI 76 to 88) per 100,000 person-years, 114 (95 % CI 104 to 124), and 47 (95 % CI 41 to 54) per 100,000 person-years in females and males, respectively. Incidence increased toward the older age groups. Clear seasonal variation was observed, two-part fractures were most common (428, 62 %), the majority of the fractures ( n = 539, 78 %) were treated nonoperatively with a sling. Conclusion The incidence of proximal humerus fractures increases with age, and we observe a seasonal variation strongly favoring winter months. It is evident that proximal humerus fractures cause considerable morbidity among elderly people and consume health care resources.